The level model of network interaction primary school students in classroom activities - Potupchik, E. G.; Hegai, L. B. (Otkrytoe Obrazovanie, 2019)
The article considers the problem of organization and methodological support of the process of formation of skills of network joint activities in primary school students. The relevance of this research problem is due to the following contradictions: between the need for a practice-oriented and controlled focus on the process of forming in young schoolchildren the skills of safe and ethical interaction in the network, as a requirement of a modern digital society and the lack of pedagogical conditions for its implementation in educational institutions; between the high potential of network interaction in the formation of digital literacy elements of elementary schoolchildren and insufficient practical and theoretical research in this area; between the didactic opportunities of joint network activities in the process of training and education in elementary school and the insufficient development of pedagogical conditions for its implementation. The purpose of the study: the development and experimental testing of the level model of network interaction of primary school children in a distributed information and educational environment. This model is based on the principle of a phased increase in the degree of activity, independence and responsibility of subjects of joint network activities, which is implemented through specially designed educational and methodological support. The problem is highlighted due to the lack of research and the lack of specialized methodological support in the field of networking in elementary school. Materials and methods. The theoretical basis of the study is the analysis of research works in the field of Internet security for schoolchildren and the psychology of primary school children, a generalization of pedagogical experience in the use of distance and network technologies in classroom activities, an analysis of the regulatory documents of primary general education. Results. The approbation of the level model of network interaction of primary schoolchildren was carried out during the 2016–2017, 2017– 2018, 2018–2019 academic years on the basis of MAOU Gymnasium No. 9 of Krasnoyarsk and secondary school No. 11 of Abakan. The study covered 105 primary school students. A complete set of educational and methodological support for the network interaction of elementary schoolchildren in computer science lessons in a distributed information and educational environment has been developed and fully tested. Conclusion. The level model of network interaction of elementary schoolchildren described in the article can be used both in the classroom and in extracurricular activities in various subject areas in elementary school. This model includes four levels of network interaction formation: interaction independently from each other without feedback, interaction independently from each other with the need for mutual control, consistent interaction with observance of the order and correctness of the task, non-linear interaction. In accordance with the developed model of network interaction, a distributed informational and educational environment of elementary school was formed and filled up on the example of the subject field “informatics”, which ensures the implementation of various types of elementary school students network interaction in classroom activities. Research materials can be replicated in general education organizations at the initial stage, and also used to improve the skills of primary school teachers and computer scientists.